i think it is if you simlify it the answer would be x+(-2)>8 your welcome aislinn
x(x+8)x^2 + 8x
4x - 8 = 8(x + 2)
The expression that represents two times the sum of p and 8 is 2(p + 8).
Y = 4 (x+8)
i think it is if you simlify it the answer would be x+(-2)>8 your welcome aislinn
Suppose the number is x. The sum of the number and two is x+2 Four times the sum is 4(x+2) The number times 8 is 8x 24 less than the number times 8 is 8x-24 4(x+2) = 8x-24 4x+8=8x-24 so 4x = 32 and x = 8
x(x+8)x^2 + 8x
the sum of 8 and 4 times a number is 36
five times the sum of a number and 8 is -15.
4x - 8 = 8(x + 2)
18 1+8=9 9x2=18
Not necessarily. If the number is 0, then the sum of 8 times the number and -192 is -192.
(3a-8) + 5x(a)
The expression that represents two times the sum of p and 8 is 2(p + 8).
4N + 8
5